Income support to families with children in Spain - Adrian Hernández; Fidel Picos (European Commission, Joint Research Centre (JRC), 2021)
Families with children receive support from the tax-benefit system to a different extent across countries. In Spain, child poverty remains high as compared to other EU countries, possibly pointing to a weaker role of the public sector in providing income support to families with children. In this paper we provide an in-depth assessment of the income support to families with children in Spain. We distinguish between three different forms of income support: (1) benefits aimed to ease the cost of raising children (child-related benefits); (2) supplements to other benefits due to having children (non-child-related benefits); and (3) tax reliefs (allowances and/or tax credits) reducing the tax burden of families with children (child-related tax reliefs). To measure these three dimensions, we use EUROMOD, the tax-benefit microsimulation model for the EU. We follow a similar methodological approach to Corak et al. (2005) and Figari et al. (2011), consisting in building a counterfactual scenario as if there were no children. For assessing the redistributive impact, we adapt the decomposition methodology of Onrubia et al. (2014), based in turn on Kakwani (1999). Our results suggest that the level of income support to families with children in Spain is low and mainly concentrated on tax reliefs, which are regressive in absolute terms. Nevertheless, the total income support to families with children is redistributive in relative terms, this effect being mainly dominated by the extent of supplements in unemployment and social assistance benefits due to having children. Child income support also reduces poverty intensity and incidence, although not to a large extent.
Keywords: H53; H23; I38; 330; poverty; child poverty; family benefits; redistribution; microsimulation; EUROMOD